Uterine inversion - an obstetrician’s nightmare: a series of 3 cases of uterine inversion and a review of management options - Jalvee, Rashmi G.; Wani, Reena J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Acute puerperal uterine inversion is an extremely rare but potentially life-threatening complication in which the uterine fundus collapses within the endometrial cavity and beyond. Although the causes of uterine inversion are unclear, several predisposing factors have been described. Maternal mortality is extremely high unless the condition is recognized and corrected. We present here a series of three cases of uterine inversion managed in our hospital over a period of 3 years. Our first case, Mrs XYZ referred to our hospital after vaginal delivery followed by postpartum collapse. The patient was in hypovolemic shock with 2nd degree uterine inversion. Second case, Mrs ABC referred to our hospital after vaginal delivery and mass coming out of the vagina. The patient had postpartum haemorrhage with 2nd degree uterine inversion. Our third case, Mrs DEF, c/o full term vaginal delivery at our hospital with 2nd degree uterine inversion with postpartum haemorrhage. In all three cases, the patients were explored in the OT under general anaesthesia and uterine reposition was done vaginally. Two of the patients required mechanical ventilation post operatively and all the patients required blood and blood product transfusion. The clinical management, treatment options and surgical nuances of management of uterine inversion are discussed.